Computer Managed Student Assessment: A Case Study - Blunt, Adrian; Dent, Beverley (Canadian Journal for the Study of Adult Education, 1999)
Computer managed assessment can provide adult and continuing education with a powerful instrument to promote program quality and instructional effectiveness and efficiency. However, few case studies are available to report on the achievements of such systems. This article reports a study of one college's experience with computer managed assessment and makes recommendations for the improvement of first generation computer assessment systems. It was observed that the assessment system was not being used as an instrument for improving program and instructional quality. Résumé L'évaluation gérée par ordinateur peut fournir aux services d'andragogie et d'éducation permanente un puissant outil de promotion de la qualité, du rendement et de l'efficacité des programmes et de l'enseignement. Or, il existe peu d'études de cas susceptibles de nous renseigner sur la portée de ces systèmes. Cet article décrit l'incursion d'un collège dans le monde de d'évaluation gérée par ordinateur, et formule quelqu.es recommandations visant l'amélioration de la première génération de systèmes de gestion informatique de l'évaluation. On a notamment observé que ces systèmes sont rarement utilisés pour régénérer la qualité des programmes et de l'enseignement.